Psychometric Properties of the Defense Mechanisms Rating Scales-Self-Report-30 (DMRS-SR-30): Internal Consistency, Validity and Factor Structure. Issue 6 (24th October 2022) - Prout, Tracy A.; Di Giuseppe, Mariagrazia; Zilcha-Mano, Sigal; Perry, J. Christopher; Conversano, Ciro
Abstract: Assessment of defense mechanisms has a longstanding history within the clinical psychology and psychopathology literature. Despite their centrality to clinical practice, there are few self-report measures that assess defenses and, those that do exist, have limitations in addressing individual defenses and levels of defensive functioning. To address this need, we investigated the psychometric properties of the Defense Mechanisms Rating Scale - Self-Report − 30 item (DMRS-SR-30) with a global, community sample of 1, 539 participants who responded to an online survey about distress and coping. Exploratory factor analysis found a three-factor model for the DMRS-SR-30 – mature, mental inhibition and avoidance, and immature-depressive. Internal consistency was high for the Overall Defensive Functioning (ODF) and the three extracted factors with coefficient alphas ranging from .75 to .90. Examination of concurrent validity with a commonly used measure of defensive functioning found significant relationships in the predicted directions. The group of immature defenses had the strongest concurrent validity ( r = .50). Finally, correlations with external criteria – including psychological distress and adverse childhood experiences – supported the convergent and discriminant validity of the DMRS-SR-30. The three factor structure of the DMRS-SR-30 has good psychometric properties. Limitations and directions for future research, as well as clinical implications, are described.